INVERSION OF DEPENDENCY PRINCIPLE IN THE SOFTWARE QUALITY: Application of the dependency Injection in the software development field - Gonçalves, Bruna Piserà; Lazaro Mendes, Oswaldo (Revista Interface Tecnológica, 2022)
Modern society more and more demands software to solve its daily problems. Because of that, computational tools change frequently. For these changes to be able to happen, it's essential to automate tests that assert whether the behavior before the changes remains the same afterward. Hence, the present paper aims to present the importance of the unit tests when it comes to software development and how the inversion of control and dependency principle enables the development of test scenarios and their respective implementations. To achieve that, a bibliographical research was made. Also, empirical examples were drawn up by the author. After that, it is possible to observe that the absence of these principles turns the unit test writing into an unfeasible task - besides having a high coupling code. It's clear from this paper that the use of the Inversion of Control and Dependency Injection principles helps to guarantee a free-dependency development, with good readability, high quality, and cohesion for the time being and also the future of the computational tool under development. Thus making the unit tests a feasible assignment in the software development field.
Keywords: Test; Unit; Dependency; Coupling; Inversion